Enhancement of RF-DC Converters Efficiency by Input Impedance Optimization - Helena Ribeiro; Diogo Matos; Nuno B. Carvalho; Apostolos Georgiadis (IEEE Access)
The Internet of Things has transformed modern technology relying on sensors powered by batteries. However, the environmental impact of batteries is a significant concern. This paper explores wireless power transfer as a viable solution to this problem. This study focuses on improving the antenna impedance to maximize the performance of the diode on the WPT receiver. The study was made with a numerical and theoretical analysis, simulations, and experimental validations. Moreover, it was demonstrated that the optimum input impedance is high impedance, approaching an open circuit. The paper concludes that designing RF-DC converters with high source impedance leads to an improvement on the rectifying efficiency.